2020
DOI: 10.1038/s41598-020-74670-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential processing of dissolved and particulate organic matter by deep-sea sponges and their microbial symbionts

Abstract: Deep-sea sponges create hotspots of biodiversity and biological activity in the otherwise barren deep-sea. However, it remains elusive how sponge hosts and their microbial symbionts acquire and process food in these food-limited environments. Therefore, we traced the processing (i.e. assimilation and respiration) of 13C- and 15N-enriched dissolved organic matter (DOM) and bacteria by three dominant North Atlantic deep-sea sponges: the high microbial abundance (HMA) demosponge Geodia barretti, the low microbial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 72 publications
3
58
1
Order By: Relevance
“…The role of host and microbiome in organic matter uptake DOM uptake DOM was rapidly incorporated by the HMA species P. angulospiculatus and the LMA species H. caerulea, and bulk rates of incorporation into sponge tissue (1.1-1.5 μmol C tracer /mmol C sponge /h and 0.4-0.6 μmol N tracer / Table S1 mmol N sponge /h; Additional file 2: Table S2) are in the range of rates presented for seven other tropical sponge species (0.3-1.2 μmol C tracer /mmol C sponge /h and 0.3-1.3 μmol N tracer /mmol N sponge /h) [30,37], confirming the viability of our tested sponges. These findings contribute to a growing body of evidence that DOM-feeding by sponges is not related to the abundance of spongeassociated microbes [8,38,49,50]. NanoSIMS analysis revealed that both symbionts and host choanocyte cells were actively involved in DOM uptake.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The role of host and microbiome in organic matter uptake DOM uptake DOM was rapidly incorporated by the HMA species P. angulospiculatus and the LMA species H. caerulea, and bulk rates of incorporation into sponge tissue (1.1-1.5 μmol C tracer /mmol C sponge /h and 0.4-0.6 μmol N tracer / Table S1 mmol N sponge /h; Additional file 2: Table S2) are in the range of rates presented for seven other tropical sponge species (0.3-1.2 μmol C tracer /mmol C sponge /h and 0.3-1.3 μmol N tracer /mmol N sponge /h) [30,37], confirming the viability of our tested sponges. These findings contribute to a growing body of evidence that DOM-feeding by sponges is not related to the abundance of spongeassociated microbes [8,38,49,50]. NanoSIMS analysis revealed that both symbionts and host choanocyte cells were actively involved in DOM uptake.…”
Section: Discussionmentioning
confidence: 60%
“…4h; Additional file 2: Table S1), indicating preferential utilisation of POMderived N by cells of the mesohyl and the mesohyl matrix, which consists primarily of the polypeptides collagen, galectin, and fibronectin-like molecules [66]. Taken together, our results suggest that POM represents a high-quality food source for host anabolism (which may include predation on microbial symbionts [39,67]), despite representing only a small portion of the natural organic matter pool and sponge diet [2,50].…”
Section: Dom and Pom Are Differentially Metabolised By The Lma Spongementioning
confidence: 77%
“…Bacteria are expected to be an even more important food source than suspended particulate matter for some glass sponges and will be assimilated efficiently (Pile and Young, 2006;Kahn et al, 2015;Bart et al, 2020a). On the Scotian Shelf an important source of bacteria can be the resuspended sediments, which are 100-1000 times enriched in heterotrophic bacteria compared to the overlaying water (Kuwae and Hosokawa, 1999).…”
Section: Food Supplymentioning
confidence: 99%
“…barretti ( n = 6) individuals were obtained from the Barents Sea (70°47N 18°03'E) around 300 m water depth on a subsequent G.O. Sars expedition in August 2018 [ 28 ]. Norwegian research expeditions do not require special permits for sample collection in this region.…”
Section: Methodsmentioning
confidence: 99%